Moderating effect of gender on factors influencing generation-y’s purchasing intention within the toy industry in Malaysia - Ong, Derek Lai Teik *; Koay, Kian Yeik * (Academy of World Business, Marketing and Management Development, 2015)
Modern age living in Malaysia has subjected people to focus on electronic device intervention in daily activities and forget about childhood memories of imagination especially with conventional toys. Store image and ambience plays a vital role in reliving these imagination and boost purchase intentions amongst the younger generation who grew up in the technology age. The research paper was designed to identify the factors of store image that affect the purchasing intention of Gen-Y’s in a toy store. Retailers need better strategy for their store image to attract these future decision makers in the toy industry. 200 respondents were surveyed around the Klang area where factor analysis and reliability test were performed to ensure the validity and reliability while multiple linear regression was used to explore the relationship between the constructs. The result of the research showed that perceived value, store physical attributes, and service quality are significant factors that influence customers purchasing intention. A further analysis on the moderating effect of gender shows that females have greater influence on the relationship between service quality and purchase intention.